2022
DOI: 10.35295/osls.iisl/0000-0000-0000-1263
|View full text |Cite
|
Sign up to set email alerts
|

Feminisms in the challenge of alternatives to punitivism: The necessary synergies in a path to be explored

Abstract: In this text, after focusing the analysis on the incidence of patriarchy in law, we want to trace the basic defining lines of the three currents of feminism that can be differentiated in relation to penal issues: prison feminism, feminist guaranteeism and anti-punitive feminism. Secondly, starting from this last thesis, some key arguments will be developed to deepen in the development of a feminism attentive to the dangers of punitive logic, the creation of frameworks that move away from punitivism as an expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, it is necessary to study its impact on socio-cultural degradation, natural resource depletion, the economic environment and pollution in Indonesia. Government support and policy interventions have a significant role in controlling tourism growth and natural resource depletion in each region [23], [29].…”
Section: The Practice Of Social Structure Synergy In Religious Touris...mentioning
confidence: 99%
“…However, it is necessary to study its impact on socio-cultural degradation, natural resource depletion, the economic environment and pollution in Indonesia. Government support and policy interventions have a significant role in controlling tourism growth and natural resource depletion in each region [23], [29].…”
Section: The Practice Of Social Structure Synergy In Religious Touris...mentioning
confidence: 99%
“…Several kinds of literature reveal that brand image can be formed and strengthened through several approaches, such as sales promotion, advertising, and service quality (Mutmainnah, 2019). Brand image is reported to be one of the factors that encourage consumers to use products or services sustainably (Lecumberri, 2022). In an empirical study, brand image is reported to be essential in increasing sales.…”
Section: Rational Choices Of Women Msmes In Kediri Regencymentioning
confidence: 99%